Development of an optimized cassava starch-based custard powder - Awoyale, W.; Sanni, Lateef O.; Shittu, T.A.; Adebowale, A.A.; Adegunwa, M.O. (Informa UK Limited, 2019)
Custard powder is a dry-formulated food product primarily made from imported corn starch in developing countries. To reduce over-dependence on corn starch, this study investigated its replacement with yellow-fleshed cassava root starch (YfCRS) in custard powder formulation. Response surface methodology was used to develop an optimized cassava starchbased custard powder based on various combinations of YfCRS (90–98%) and whole egg powder (WEP) (2–10%). The result showed that the blends of YfCRS and WEP led to custard powder with wide functional, physicochemical, chemical, and micronutrient properties, with sensorily acceptable gruel. The second order response surface regression model accurately predicted most of these quality parameters (R2 > 0.90). The optimum formulation achieved to produce an acceptable custard was 90% YfCRS and 6.07% WEP. Therefore, this study showed that YfCRS might be a very good replacement for corn starch in the production of an acceptable custard.